1999
DOI: 10.1002/etc.5620180412
|View full text |Cite
|
Sign up to set email alerts
|

Improved method for estimating bioconcentration/bioaccumulation factor from octanol/water partition coefficient

Abstract: Abstract-A compound's bioconcentration factor (BCF) is the most commonly used indicator of its tendency to accumulate in aquatic organisms from the surrounding medium. Because it is expensive to measure, the BCF is generally estimated from the octanol/water partition coefficient (K ow ), but currently used regression equations were developed from small data sets that do not adequately represent the wide range of chemical substances now subject to review. To develop an improved method, we collected BCF data in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
155
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(168 citation statements)
references
References 29 publications
6
155
0
1
Order By: Relevance
“…Clearly, a calibration time of 60 d, a time duration often used in fish exposure experiments [5][6][7], can yield reasonable accuracy when C w is determined with the laboratory-calibrated C pe /C w . We previously obtained a curvilinear relationship between the logarithm of PDMS-water partition coefficient (log K f ) and log K OW for PCBs with the turning point at log K OW approximately equal to 7 to 7.5 [17,18], which is similar to the fieldobserved correlations between log-based bioconcentration factor and log K OW [19][20][21]. This curvilinearity was attributed to the difference in the Gibbs free energies for cavity formation in PDMS and octanol that can become significant for larger molecules [18].…”
Section: Sorption Kinetics Of Target Bde Congenerssupporting
confidence: 67%
“…Clearly, a calibration time of 60 d, a time duration often used in fish exposure experiments [5][6][7], can yield reasonable accuracy when C w is determined with the laboratory-calibrated C pe /C w . We previously obtained a curvilinear relationship between the logarithm of PDMS-water partition coefficient (log K f ) and log K OW for PCBs with the turning point at log K OW approximately equal to 7 to 7.5 [17,18], which is similar to the fieldobserved correlations between log-based bioconcentration factor and log K OW [19][20][21]. This curvilinearity was attributed to the difference in the Gibbs free energies for cavity formation in PDMS and octanol that can become significant for larger molecules [18].…”
Section: Sorption Kinetics Of Target Bde Congenerssupporting
confidence: 67%
“…Its tissues contain signi"cantly more toxic congeners than "sh which can be explained by the birds' enhanced metabolic capacity. In aquatic animals, biotransformation of a chemical substance assimilated from an animal's environment has the e!ect of increasing the substance's net elimination rate and thus decreasing the equilibrium level of the substance in the organism (Meylan et al, 1999). Fish have the same complement of enzymes as do mammals, including those catalyzing phase I (oxidative, reductive, and hydrolytic) and phase II (conjugative) reactions, although activity is often lower than in birds (Spacie et al, 1983;De Wolf et al, 1992;De Bruijn et al, 1993;James, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Normalizing to lipid content can eliminate some interspecies variation in BCF values, but it has also been reported that lipid content may not be as important a determinant of bioconcentration potential as previously thought (Barron, 1990). In aquatic animals, biotransformation of a chemical substance assimilated from an animal's environment has the e!ect of increasing the substance's net elimination rate and thus decreasing the equilibrium level of the substance in the organism (Meylan et al, 1999). Before 1962, the lake in the present study (Ya-Er Lake in China) was an oligotrophic lake.…”
Section: Introductionmentioning
confidence: 99%
“…The Stockholm convention on POPs (3) and other chemical management programs categorize chemicals with BCF or BAF higher than 5000 (wet weight basis) as bioaccumulative. Although usually calculated on a wet weight basis (2,4), BAFs and BCFs change depending on the lipid content of the organism. Therefore, lipid-normalized BAF and BCF values (eq 1) are more useful when comparing across animals, as the variation due to variable lipid content is eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…BCF on a wet weight basis can be predicted from the chemical's octanol-water partition coefficient (KOW), by models such as BCFWIN used by the U.S. Environmental Protection Agency (USEPA) (4). In absence of environmental measurements of a chemical in biota and water to calculate BAFs, BCFs predicted from KOWs are useful tools for exposure and risk assessments of new chemicals; however, for animals with dietary exposure and uptake of POPs they may be underpredicted.…”
Section: Introductionmentioning
confidence: 99%